A study of antimicrobial and antifungal activity of 2-((5-(2-bromophenyl)-4-substituted-4H-1,2,4-triazol-3-yl)thio)acetates - A. A. Safonov; A. V. Nevmyvaka (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Bacteria and fungi are among the most ancient creatures found on Earth. Since the advent of medicine, humankind has always sought new means and ways to combat these microorganisms. In modern scientific society, the tendency to seek new antimicrobial and antifungal agents is only increasing. 1,2,4-triazole derivatives, among which effective drugs and new molecules have already been found, make quite an interesting platform for the creation of new antifungal and antimicrobial agents.